The linkages between economic growth, employment and poverty reduction / Farah Adlina Mokter - Mokter, Farah Adlina (2007)
The purpose of this research is to investigate the linkages between economic growth, employment and poverty reduction. It will determine the effect of economic growth and employment towards poverty reduction. This research will study the important role of employment as to determine the inter-relationship of economic growth and. poverty reduction. The data are GDP percapita, employment and poverty rate. The variables will be analyzed for different years for each country because the data for poverty is very limited. This study will be used the Multiple Regression Model for the statistical tool. The statistical software that has been used to analyze the data is the Statistical Package for Social Science (SPSS). Sustained economic growth has a positive impact on poverty reduction. When economic growth generates employment for the poor, it will raise the labor demand, which help the poor who are unemployed find jobs and earn enough income to meet their basic needs. And if labor productivity of the poor and marginal return for the poor increase from economic growth, the implication is an increase in their income.